Union Budget 2021 of the People by the People, for the People - R. Pazhanisamy (Department of Humanities and Social Sciences (HSS), Jain University Global Campus; ZBW - Leibniz Information Centre for Economics, 2021)
In spite of the pandemic pressure to limit the use of the resources both internally and outside the economies policymakers all over the globe, compete each other's to recover the economic growth with a v shape through various planned activities on mission mode. Social budgeting is found as one of the most effective way to achieve these objective (United Nation 2020) which has not been effectively practiced and fully implemented widely across the economies due multifaceted and dynamic problems encountered by the public which limits the outlining of the elements of social budget within the usual budgetary framework. This involves various issues of inter and intra allocation of the public expenditures and the source of revenue. With a view to reflect the public priorities in the budget information on how the policymakers collect the public opinion and how they use it rationally which is not available across the literature and leaves a considerable gap in research. In this context an attempt is made in this policy brief to fill this gap in research. During the pandemic period the demand for such above approach particularly in a democratic economy like India to implement social budget becomes inevitable as it is the government of the people, by the people for the public. Using the secondary data from the ministry of finance the trend of the public expenditure and revenue the elements of social budgeting in India is outlined and the possibility of the effective implementations of the social budget 2021 is given in simplest way that everyone can be understand.
Additional information: Disclaimer: The views appeared in the works are of the authors only. In no way it reflects the institutions in which they belong to.
Keywords: H2; H5; H6; O2; I3; E6; 330; Union budget 2021; India's budget 2021; Democratic budget; Social budget; Pandemic budget